ナンキョク マクマードサウンド チイキ ビーコン ソウ グン ノ コチジキ ガクテキ ケンキュウ - 船木, 實; フナキ, ミノル; Funaki, Minoru (1983)
P(論文) 南極マクマードサウンド地域には, デボン紀からジュラ紀にかけての, 主に砂岩層を主体とするビーコン層群が広く分布する。この地域内のシアス山, ノブヘッド山, アランヒルズ, それにフレミング山から合計216個の古地磁気学用岩石試料を採集した。それぞれの採集地の地層は, デボン紀の初期あるいはそれ以前, デボン紀, 二畳紀末から三畳紀初期, それに三畳紀である。この地域の各所にジュラ紀のフェラードレライトの岩床の貫入が見られ, 採集された試料が堆積残留磁気(DRM)を持つのか, 熱残留磁気(TRM)を持つのかを調べるため, 自然残留磁気(NRM)の交流および熱消磁, ARMおよびTRMの獲得の様子, それにARMの交流消磁を行った。実験結果, シアス山の試料はいずれも安定なTRMを持ち, デボン紀に獲得したDRMは完全に失われている。ノブヘッド山の試料も基本的にシアス山の試料と同じである。アランヒルズの一部の試料は安定なDRMを持ち, ドレライトの岩床による影響は, ほとんどなかったと考えられる。フレミング山の試料のうち, 安定なNRMを持つ試料は, TRMを獲得していると考えられる。以上の結果, あらたに二畳紀末-三畳紀にかけての東南極大陸のVGPが決定された。この位置はジュラ紀のVGPにきわめて近い位置にあり, この間東南極大陸は大きく移動しなかったと考えられる。これはオーストラリアから得られた結果と一致し, 少なくとも両大陸はジュラ紀まで連続した大陸だったことを示している。 A total of 216 paleomagnetic samples of the Beacon Group (sandstone) were collected from Mt. Circe, Mt. Knobhead, Allan Hills and Mt. Fleming. The respective sedimentary sequences are Pre- or Early-Devonian, Devonian, Permo-Triassic and Triassic. The representative samples were tested for NRM stability against AF and thermal demagnetization, ARM and TRM acquisition, and AF demagnetization of ARM. The following results were obtained. The samples from Mt. Circe and Mt. Knobhead have stable NRM of parallel direction to that of the Ferrar dolerite. From this we conclude that these samples were remagnetized in the Jurassic Age and the primary magnetization disappeared. The samples from Mt. Fleming were also remagnetized by the dyke of the Ferrar dolerite or do not have stable NRM. However, parts of the samples from the Allan Hills have stable depositional remanent magnetization (DRM) of the Permo-Triassic Age. The direction of NRM for these samples is parallel to that of the Ferrar dolerite in the Jurassic Age. This suggests that East Antarctica had no shift of VGP. This conclusion is consistent with the results on the Mesozoic Age in Australia. Thus Australia must have been linked to Antarctica at least up to the Jurassic Age. departmental bulletin paper